PENGARUH PENGGUNAAN SMARTPHONE TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (Analisis Kuantitatif terhadap Siswa Kelas VIII di SMPN 4 Teluk Kuantan) - Kurnia Dila Okviawati; Zulhaini Zulhaini; Ikrima Mailani (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
This research is motivated by the rapid development of information and communication technology at this time. So that various terms emerge to classify these products, one of which is a smartphone, also known as a gadget; small electronic devices that have special functions, included in the learning process by elementary to high school students. However, due to the lack of supervision, utilization and optimization of smartphones for positive purposes, so many students are wrong in using smartphones.Based on the background and phenomenon above, this study aims to determine whether there is an influence of the use of smartphones on student achievement in class VIII on Islamic Religious Education subjects at SMP Negeri 4 Teluk Kuantan. This research is a quantitative study with a causal associative level of explanation, carried out at SMP Negeri 4 Teluk Kuantan. Data collection techniques used were questionnaires with instruments in the form of questionnaires, interviews, observation and documentation. Data analysis uses simple linear regression formula which is processed using SPSS 17.0 software. The results showed that there was no positive and significant effect of smartphone usage, in the significance test found the equation that the value (Sig.) 0.149> probability 0.05 so that it was concluded there was no influence of the variable X on Y.